Psikologi Islam Kontemporer - Sari Narulita (Jurnal Studi Al-Qur'an, 2015)
This study stems from Dr. Zakiah Drajat who began to introduce the psychology of religious views. However, it was not until 1994 that through the national symposium, Islamic psychology enthusiasts were finally collected and came to an agreement to name the new knowledge in the name of Islamic psychology, after many names were proposed, among them the Psychology of Qur'ani, Psychology of Tasawwuf and so on. Islam is a concept that is outside of its adherents; but as a belief, Islam became part of its adherents. To deepen the psychology of the Muslims, it takes a separate study that has not been touched by the study of western psychology. This study is the focus of the study of Islamic psychology. Keywords: Islamic Psychology, Psychiatry, Western PsychologyAbstrak Kajian ini bermula dari usaha Dr. Zakiah Drajat yang mulai mengenalkan psikologi dari tinjauan agama. Namun baru pada tahun 1994, melalui simposium nasional, para peminat psikologi Islam akhirnya dikumpulkan dan muncullah kesepakatan untuk menamakan pengetahuan baru tersebut dengan nama psikologi Islam, setelah sebelumnya, banyak nama diusulkan, di antaranya adalah Psikologi Qurâ€™ani, Psikologi Tasawwuf dan lain sebagainya. Islam adalah konsep yang berada di luar diri pemeluknya; namun sebagai keyakinan, Islam menjadi bagian dari pemeluknya. Untuk mendalami kejiwaan kaum muslim, dibutuhkan kajian tersendiri yang selama ini tidak tersentuh oleh kajian psikologi barat. Kajian inilah yang menjadi fokus kajian psikologi Islam. Kata Kunci: Psikologi Islam, Kejiwaan, Psikologi Barat